Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18052/www.scipress.com/sfp.8.29
|View full text |Cite
|
Sign up to set email alerts
|

Ripening Stage Affects the Quality of Fresh and Dehydrated Pineapples (<i>Ananas comosus </i>(L.) Merr.)<i> cv. </i>Mauritius in Sri Lanka

Abstract: Pineapple (Ananas comosus (L.) Merr.) being a non climacteric fruit, its flavor and sugar content does not increase after harvesting. Thus, the maturity stage at harvesting affects the quality of pineapples after harvesting. This study was conducted to compare the quality parameters at four different ripening stages of pineapple (cultivar Mauritius-Queen type) and their effect on sensory properties after dehydration. Pineapples were harvested at dark green, 50% yellow, 75% yellow and 100% yellow color stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As pineapple maturity increases, so does the pH value, while titratable acidity decreases due to depletion of acids caused by metabolic reaction during ripening process (Table 2). The balance of sweet and sour taste of fruit is determined by the ratio of total soluble solids to titratable acidity (TSS/TA) (Kumara & Hettige, 2020; Mandal et al., 2015; Zhang et al, 2020). The higher TSS/TA ratio in the Index 7 indicates the sweeter or less sour taste of the pineapple.…”
Section: Resultsmentioning
confidence: 99%
“…As pineapple maturity increases, so does the pH value, while titratable acidity decreases due to depletion of acids caused by metabolic reaction during ripening process (Table 2). The balance of sweet and sour taste of fruit is determined by the ratio of total soluble solids to titratable acidity (TSS/TA) (Kumara & Hettige, 2020; Mandal et al., 2015; Zhang et al, 2020). The higher TSS/TA ratio in the Index 7 indicates the sweeter or less sour taste of the pineapple.…”
Section: Resultsmentioning
confidence: 99%
“…erefore, the "MD-2" type was expected to have a high value compared to other cultivars [24,26]. e TSS and TA were also increased with the ripening stage [25].…”
Section: Discussionmentioning
confidence: 98%
“…e usual values of the pH in low acid hybrids fall in the range of 3.3 to 4.0, decreasing as the fruit gets closer to harvest [22][23][24][25]. erefore, the "MD-2" type was expected to have a high value compared to other cultivars [24,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend continued until the end of the storage period. Kumara and Hettige (2020) reported that the highest TSS content of 17.75  0.67 was seen in the 100% yellow tubercles stage in the pineapple 'Mauritius'.…”
Section: Total Soluble Solidsmentioning
confidence: 99%